Linear Motion Materials on Authentic Learning in Collaborative Problem-Solving Model: Validity Aspects - Nadrah Nadrah (Postgraduate, University of Mataram, 2023)
The collaborative problem-solving model has advantages in providing facilities for individuals to work effectively in a group and apply their problem-solving skills in various situations and conditions. Problem-solving and collaboration skills are needed in the physics learning process, yet a lack of authentic learning-based resources and inappropriate learning models causes students to struggle to grasp the subject and solve issues collaboratively. The study aims to describe the theoretical validity of the development product in the form of authentic learning-based linear motion teaching materials using a collaborative problem-solving model. The Research and Development model used is ASSURE. The data was obtained through the validation sheet of teaching materials assessed by three validators. The validation findings indicate that the generated instructional materials are very valid, with an average score of 3.55. Thus, it is concluded that the linear motion teaching material based on authentic learning using a collaborative problem-solving model can be tested in the learning process. Thus, the developed teaching materials can be tried out in classroom learning and used as a learning resource for students to solve problems collaboratively.